Magnitude of antigen-specific T-cell immunity the month after completing vaccination series predicts the development of long-term persistence of antitumor immune response - Mary L Disis; John B Liao; Jessica L Reichow; Lupe G Salazar; Sasha E Stanton; Katie M Hitchcock-Bernhardt; James Y Dai; Jong-Baeck Lim; Theodore A Gooley (Journal for ImmunoTherapy of Cancer)
Background For best efficacy, vaccines must provide long-lasting immunity. To measure longevity, memory from B and T cells are surrogate endpoints for vaccine efficacy. When antibodies are insufficient for protection, the immune response must rely on T cells. The magnitude and differentiation of effective, durable immune responses depend on antigen-specific precursor frequencies. However, development of vaccines that induce durable T-cell responses for cancer treatment has remained elusive.Methods To address long-lasting immunity, patients with HER2+ (human epidermal growth factor receptor 2) advanced stage cancer received HER2/neu targeted vaccines. Interferon-gamma (IFN-γ) enzyme-linked immunosorbent spot measuring HER2/neu IFN-γ T cells were analyzed from 86 patients from three time points: baseline, 1 month after vaccine series, and long-term follow-up at 1 year, following one in vitro stimulation. The baseline and 1-month post-vaccine series responses were correlated with immunity at long-term follow-up by logistic regression. Immunity was modeled by non-linear functions using generalized additive models.Results Antigen-specific T-cell responses at baseline were associated with a 0.33-log increase in response at long-term follow-up, 95% CI (0.11, 0.54), p=0.003. 63% of patients that had HER2/neu specific T cells at baseline continued to have responses at long-term follow-up. Increased HER2/neu specific T-cell response 1 month after the vaccine series was associated with a 0.47-log increase in T-cell response at long-term follow-up, 95% CI (0.27, 0.67), p=2e-5. 74% of patients that had an increased IFN-γ HER2 response 1 month after vaccines retained immunity long-term. As the 1-month post-vaccination series precursor frequency of HER2+IFN-γ T-cell responses increased, the probability of retaining these responses long-term increased (OR=1.49 for every one natural log increase of precursor frequency, p=0.0002), reaching an OR of 20 for a precursor frequency of 1:3,000Conclusions Patients not destined to achieve long-term immunity can be identified immediately after completing the vaccine series. Log-fold increases in antigen-specific precursor frequencies after vaccinations correlate with increased odds of retaining long-term HER2 immune responses. Further vaccine boosting or immune checkpoint inhibitors or other immune stimulator therapy should be explored in patients that do not develop antigen-specific T-cell responses to improve overall response rates.